Phenolic compound profile by UPLC-MS/MS and encapsulation with chitosan of Spondias mombin L. fruit peel extract from Cerrado hotspot-Brazil - Brito, Giovanna Oliveira de (2022)
Taperebá (Spondias mombin L.) is a native species of the Brazilian Cerrado that has shown important characteristics such as a significant phenolic compound content and biological activities. The present study aimed to characterize the phenolic compound profile and antioxidant activity in taperebá peel extract, as well as microencapsulating the extract with chitosan and evaluating the stability of the microparticles. The evaluation of the profile of phenolic compounds was carried out by UPLC-MS/MS. The in vitro antioxidant activity was evaluated by DPPH and ABTS methods. The microparticles were obtained by spray drying and were submitted to a stability study under different temperatures. In general, the results showed a significant content of polyphenols and antioxidant activity. The results of UPLC-MS/MS demonstrated a significant content of polyphenols in taperebá peel, highlighting the high content of ellagic acid and quercetin compounds. There was significant retention of phenolic compounds when microencapsulated, demonstrating high retention at all evaluated temperatures. This study is the first to microencapsulate the extract of taperebá peel, in addition to identifying and quantifying some compounds in this fruit.